Karakteristik Kepemimpinan dalam Perspektif Al-Qur’an Surat Al-Baqarah Ayat 30 - Rochaeni, Reni; Ramadhan, Raffly Gilang; Asrin, Lulu Khulwatul Jannah (Jurnal Penelitian Multidisiplin Ilmu, 2024)
This research examines the interpretation of Al-Baqarah verse 30 which explains the role of humans as caliphs on earth, both from the perspective of classical and modern interpretations. The method used is a literature study by analyzing the interpretations of major sources such as Ibn Katsir and Sayyid Qutb. The results show that although humans have the potential to do damage, they are also given the ability to do greater good. Classical commentaries emphasize that humans are appointed as caliphs to carry out God's will, while modern commentaries highlight the moral and social responsibilities of humans in maintaining harmony with nature and others. This study concludes that the duty of the khalifah is not only to manage the earth, but also to maintain social welfare and the sustainability of nature. Translated with DeepL.com (free version)